An Investor Protection in Cases of Sharia-Labeled Bogus Investments: A Study of Sharia Economic Law and Financial Services Authority - Mashuddin, Aeky Rezkiah Fattah; Meriska (Prodi Hukum Ekonomi Syariah, Fakultas Syariah, IAIN Palopo, 2025)
Purpose – This study aims to analyze the legal protection mechanisms for victims of bogus investments labeled as sharia from the perspective of Islamic Economic Law and to assess the effectiveness of regulations issued by the Financial Services Authority (OJK) in preventing and addressing illegal investment practices. The novelty of this research lies in its cross-case comparative analysis including PT CSI, Dream for Freedom (D4F), Abu Tours, GTIS, First Travel, and Pandawa which demonstrates that sharia-labeled bogus investments are not random incidents but constitute a systematic pattern of deception exploiting sharia attributes, low literacy levels, and regulatory gaps. This comparative approach has rarely been applied in previous studies, thereby providing a deeper understanding of the structural nature of bogus investment schemes operating under a sharia label. Method – This study employs a qualitative method with an empirical approach to provide an in-depth description of the legal protection mechanisms for victims of bogus investments labeled as sharia-based. Primary data were obtained through in-depth interviews with OJK officials, law enforcement officers, academics, and victims, while secondary data were collected through document analysis of relevant regulations. The data were analyzed to identify patterns of legal protection, the effectiveness of OJK’s supervisory framework. Result – The findings of the research indicate that bogus investments labeled as sharia-compliant fundamentally violate the principles of Islamic Economic Law because they contain elements of gharar (uncertainty), maysir (speculation), and tadlis (deception), while also exploiting the low level of financial and sharia literacy within society. The study also found that regulations and oversight by the Financial Services Authority (OJK) including education, literacy programs, legality verification, and enforcement through the Investment Alert Task Force have played a role in providing both preventive and repressive legal protection. Implication – As a practical implication, the effectiveness of these protections remains limited by regulatory gaps, OJK’s restricted authority over illegal entities, and the increasing complexity of bogus schemes. In addition, interview results show that synergy between OJK, the police, and the Sharia Supervisory Board still needs to be strengthened to maximize the restoration of victims’ rights and prevent similar cases in the future.